Magnetron sputtering modified biomedical titanium alloy and preparation method thereof
By forming a porous Nb coating on the surface of the titanium alloy, the problem of frictional corrosion of titanium alloy in biological medical devices is solved, and its frictional corrosion resistance and service life are significantly improved.
Patent Information
- Application Number
- CN202411443537.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In biological medical devices, titanium alloys are caused by low surface hardness and poor wear resistance, which leads to frictional wear and corrosion, which in turn causes frictional corrosion and affects its service life.
Magneto-controlled sputtering technology is used to form a porous structure Nb coating with a thickness of 22 to 25 μm on the surface of the titanium alloy substrate. The coating consists of nanoparticles with particle size of 5 to 20 nm to improve its surface hardness and wear resistance.
It significantly improves the friction corrosion resistance of the surface of titanium alloy, reduces the friction coefficient and material loss, enhances the microhardness and micro-wear resistance, and ensures long-term and stable use under the combined action of corrosion and wear.
Smart Images

Figure CN119320927A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical titanium alloys, and in particular to a biomedical titanium alloy modified by magnetron sputtering and a preparation method thereof. Background Art
[0002] Titanium alloy TC4 (Ti6Al4V) is widely used in biomedical devices, orthopedic implants and other fields due to its high strength, high biocompatibility, low density and other advantages. However, titanium alloys have the problems of low surface hardness and relatively poor wear resistance. In actual engineering, it has been found that relative movement will occur between titanium alloy connecting parts, causing friction and wear, such as the contact interface of the head and neck parts of artificial hip joints. This damage will evolve into friction corrosion under the action of body fluid corrosion. Friction corrosion refers to the degradation of the material surface caused by the combined action of corrosion and wear. Friction corrosion of titanium alloys will cause surface material loss, deteriorate the service state of components, and even cause component failure. Therefore, it is very important to improve the surface performance of titanium alloys and reduce friction corrosion damage on their surfaces.
[0003] Magnetron sputtering coating technology provides a solution for improving the surface performance of titanium alloys. Magnetron sputtering coating technology can cause the target material to sputter under the action of an electric field and deposit on the substrate to form a coating. Magnetron sputtering coating technology has the characteristics of high coating purity, controllable coating thickness, and good film-substrate bonding. It can form a dense protective layer on the surface of the substrate, thus gaining wide application. However, the existing technology focuses on the single high-temperature oxidation resistance, corrosion resistance and wear resistance of titanium alloy surface coatings. The friction corrosion performance of titanium alloys under the combined action of corrosion and wear has not been reported so far. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a biomedical titanium alloy modified by magnetron sputtering with good friction and corrosion resistance, a preparation method thereof and a friction and corrosion resistance testing method.
[0005] In order to achieve the above object, according to the first aspect of the present invention, a biomedical titanium alloy modified by magnetron sputtering is provided, and the technical solution is as follows:
[0006] A biomedical titanium alloy modified by magnetron sputtering comprises a titanium alloy substrate and a Nb coating on the surface of the titanium alloy substrate.
[0007] As a further improvement of the above-mentioned biomedical titanium alloy modified by magnetron sputtering: the thickness of the Nb coating is 22 to 25 μm.
[0008] As a further improvement of the above-mentioned biomedical titanium alloy modified by magnetron sputtering: the Nb coating has a porous structure formed by the accumulation of nanoparticles with a particle size of 5 to 20 nm, and the pore diameter is 3 to 15 nm.
[0009] As a further improvement of the above-mentioned biomedical titanium alloy modified by magnetron sputtering: the mass fraction of each element in the titanium alloy substrate is: 6.05% aluminum, 3.95% vanadium, 0.11% iron, 0.014% carbon, 0.14% oxygen, 0.006% nitrogen, 0.001% hydrogen, and 89.729% titanium; the tensile strength of the titanium alloy substrate is 860MPa, the yield strength is 795MPa, the elongation is 12%, the elastic modulus is 110GPa, and the Poisson's ratio is 0.3; the surface roughness of the titanium alloy substrate is Ra≤0.1μm.
[0010] In order to achieve the above object, according to the second aspect of the present invention, a method for preparing biomedical titanium alloy modified by magnetron sputtering is provided, and the technical scheme is as follows:
[0011] The method for preparing biomedical titanium alloy modified by magnetron sputtering described in the first aspect above comprises the following steps: pretreatment of titanium alloy substrate; using Nb metal sheet as target material, the surface of titanium alloy substrate as deposition surface, argon gas as working gas, and sputtering Nb atoms in Nb metal sheet to the surface of titanium alloy substrate under the action of electric field, thus forming Nb coating on the surface of titanium alloy substrate.
[0012] As a further improvement of the above-mentioned preparation method of the biomedical titanium alloy modified by magnetron sputtering: the purity of the Nb metal sheet is above 99.9%.
[0013] As a further improvement to the preparation method of the above-mentioned magnetron sputtering modified biomedical titanium alloy: the titanium alloy substrate is pretreated as follows: first, it is polished on a polishing machine with 600#, 1000#, 1500#, and 2000# sandpaper in sequence; then, it is precisely polished using W2.5 diamond grinding paste and a 3000# roughness cloth grinding wheel; then, it is ultrasonically cleaned in anhydrous ethanol for two minutes; and then, it is pre-sputtered with argon for 30 minutes.
[0014] As a further improvement of the above-mentioned preparation method of magnetron sputtering modified biomedical titanium alloy: radio frequency sputtering is adopted; the diameter of the Nb metal sheet is 50 mm and the thickness is 5 mm; the distance between the surface of the Nb metal sheet and the surface of the biomedical titanium alloy substrate is 40 mm; the working gas is argon, the purity of argon is 99.99%, and the argon flow rate is 80 sccm; the working pressure is 2 Pa, the discharge voltage is 200 V, the applied power is 200 W, the deposition time is 1500 min, and the sputtering angle is 25°.
[0015] In order to achieve the above object, according to the third aspect of the present invention, a method for testing the friction and corrosion resistance of biomedical titanium alloy modified by magnetron sputtering is provided, and the technical scheme is as follows:
[0016] The method for testing the friction and corrosion resistance of biomedical titanium alloy modified by magnetron sputtering described in the first aspect is characterized by: conducting the friction and corrosion test in a micro-motion test device, using CoCrMo alloy as the counter-friction material, in a simulated body fluid.
[0017] As a further improvement of the test method for the friction and corrosion resistance of the above-mentioned magnetron sputtering modified biomedical titanium alloy: the tensile strength of the CoCrMo alloy is 1507MPa, the yield strength is 962MPa, the elongation is 20%, the elastic modulus is 200GPa, and the Poisson's ratio is 0.3; the mass fraction of each element of the CoCrMo alloy is: chromium element is 28.10wt%, molybdenum element is 5.90wt%, nickel element is 0.88wt%, iron element is 0.65wt%, manganese element is 0.63wt%, silicon element is 0.22wt%, carbon element is 0.25wt%, nitrogen element is 0.12wt%, and cobalt element is 63.25%; the concentration of each component in the simulated body fluid is: Na + 142.0mM, K + 5mM, Mg 2+ 1.5mM, Ca 2+ 2.5mM, Cl - 147.8mM, HCO3 - 4.2mM, HPO4 2- 1.0mM, SO4 2- is 0.5mM.
[0018] The present invention has the following beneficial effects:
[0019] Niobium metal has the advantages of stable chemical properties, good biocompatibility, strong corrosion resistance, good high-temperature oxidation resistance, etc. The present invention uses magnetron sputtering technology to successfully introduce niobium into the surface of a titanium alloy substrate for the first time, forming a uniformly distributed and densely organized Nb coating. The coating surface and interior are free of cracks, delamination and other damage, and the coating-substrate bonding is good.
[0020] It has been verified that, compared with the titanium alloy substrate without surface modification, the Nb coating introduced in the present invention has a high hardness, reduces the friction coefficient and friction corrosion material loss, open circuit potential change and corrosion current on the surface of the titanium alloy substrate. Therefore, the biomedical titanium alloy with Nb surface modification prepared by the present invention has significantly better microhardness, fretting wear resistance and corrosion resistance, exhibits excellent friction corrosion resistance under the combined action of corrosion and wear, can be used stably for a long time, and has excellent practicality.
[0021] In the above-mentioned friction and corrosion resistance test method, CoCrMo alloy has very high tensile strength and yield strength, which enables it to withstand high loads without plastic deformation during friction. CoCrMo alloy has excellent wear resistance, which is very important for reducing wear between friction pairs. The higher elastic modulus enables CoCrMo alloy to have smaller deformation under load, which improves the stability of the friction pair system. CoCrMo alloy contains higher chromium and molybdenum, which enables the alloy to form a stable passivation film in a corrosive environment, improving its corrosion resistance. The composition design of the simulated body fluid is very close to that of the human body fluid, and can truly reflect the behavior of the material in the actual physiological environment. The simulated body fluid contains a variety of ions (such as Na + , K + Mg 2+ , Ca 2+ These ions can react with the surface of metal materials in complex electrochemical reactions, simulating the corrosion process under actual physiological conditions. It can be seen that the friction and corrosion resistance test method of the present invention can truly and effectively evaluate the friction and corrosion resistance of titanium alloys in actual use environments by using CoCrMo alloy as the wear pair material in the micro-motion test device and conducting friction and corrosion tests in simulated body fluids.
[0022] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. Additional aspects and advantages of the present invention will be partially given in the following description, partially become apparent from the following description, or be learned through the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings constituting a part of the present invention are used to assist in understanding the present invention. The contents provided in the drawings and their related descriptions in the present invention can be used to explain the present invention, but do not constitute improper limitations on the present invention. In the drawings:
[0024] Figure 1 This is a low-magnification SEM photograph of the surface of the Nb coating-titanium alloy of the present invention.
[0025] Figure 2 This is a medium-magnification SEM photograph of the surface of the Nb coating-titanium alloy of the present invention.
[0026] Figure 3 This is a high-magnification SEM photograph of the surface of the Nb coating-titanium alloy of the present invention.
[0027] Figure 4 This is a low-magnification SEM photograph of the cross section of the Nb coating-titanium alloy of the present invention.
[0028] Figure 5 This is the EDS line scan spectrum of the Nb coating-titanium alloy of the present invention.
[0029] Figure 6 It is a microhardness comparison diagram of the Nb coating-titanium alloy and the titanium alloy substrate of the present invention.
[0030] Figure 7 It is a comparison chart of the friction coefficients of the Nb coating-titanium alloy and the titanium alloy substrate of the present invention.
[0031] Figure 8 It is a comparison chart of the material loss of the Nb coating-titanium alloy and the titanium alloy substrate of the present invention.
[0032] Fig. 9 It is a comparison diagram of the open circuit potential of the Nb coating-titanium alloy and the titanium alloy substrate of the present invention.
[0033] Fig.10 It is a comparison diagram of the polarization curves of the Nb coating-titanium alloy and the titanium alloy substrate of the present invention. DETAILED DESCRIPTION
[0034] The present invention is described clearly and completely below in conjunction with the accompanying drawings. A person skilled in the art will be able to implement the present invention based on these descriptions. Before describing the present invention in conjunction with the accompanying drawings, it should be particularly noted that:
[0035] The technical solutions and technical features provided in each part of the present invention, including the following description, may be combined with each other if there is no conflict.
[0036] In addition, the embodiments of the present invention involved in the following description are generally only a part of the embodiments of the present invention, rather than all the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0037] About the terms and units in the present invention: The terms "include", "have" and any variations thereof in the description and claims of the present invention and related parts are intended to cover non-exclusive inclusions.
[0038] The embodiment of the biomedical titanium alloy modified by magnetron sputtering and the preparation method thereof of the present invention comprises the following steps:
[0039] (1) Pretreatment of titanium alloy substrate
[0040] The mass fractions of the elements in the titanium alloy substrate are: 6.05% aluminum, 3.95% vanadium, 0.11% iron, 0.014% carbon, 0.14% oxygen, 0.006% nitrogen, 0.001% hydrogen, and 89.729% titanium.
[0041] The titanium alloy substrate has a tensile strength of 860 MPa, a yield strength of 795 MPa, an elongation of 12%, an elastic modulus of 110 GPa, and a Poisson's ratio of 0.3;
[0042] The steps for pretreating the surface of the titanium alloy substrate are: first, polish it with 600#, 1000#, 1500#, and 2000# sandpaper in a polishing machine, and then use W2.5 diamond grinding paste and 3000# roughness cloth grinding disc for precision polishing, so that the surface roughness Ra of the titanium alloy substrate is finally made ≤0.1μm; before magnetron sputtering, the titanium alloy substrate is ultrasonically cleaned in anhydrous ethanol for two minutes to remove impurities on the surface of the substrate, which helps to improve the coating quality.
[0043] (2) Magnetron sputtering reaction
[0044] Using Nb metal sheet as the target material, the surface of the titanium alloy substrate as the deposition surface, and argon as the working gas, the Nb atoms in the Nb metal sheet are sputtered onto the surface of the titanium alloy substrate under the action of the electric field, that is, a Nb coating is formed on the surface of the titanium alloy substrate. The obtained material is named Nb coating-titanium alloy and stored in a sterile drying oven at 25°C.
[0045] Specifically, radio frequency sputtering is used; the diameter of the Nb metal sheet is 50 mm, the thickness is 5 mm, and the purity is 99.99%; the distance between the surface of the Nb metal sheet and the surface of the titanium alloy substrate is 40 mm; the working gas is argon, the purity of argon is 99.99%, and the argon flow rate is 80 sccm; the working pressure is 2 Pa, the discharge voltage is 200 V, the applied power is 200 W, and the sputtering angle is 25°; the deposition time is 1500 min, that is, a Nb coating is generated on the surface of the titanium alloy substrate.
[0046] Figure 1 This is a low-magnification SEM photograph of the surface of the Nb coating-titanium alloy of the present invention. Figure 2 This is a medium-magnification SEM photograph of the surface of the Nb coating-titanium alloy of the present invention. Figure 3 This is a high-magnification SEM photograph of the surface of the Nb coating-titanium alloy of the present invention.
[0047] like Figure 1-3 As shown, the surface material of the Nb coating is evenly distributed and dense, without any damage such as cracks or delamination. The Nb coating has a porous structure, which is composed of nanoparticles with a particle size of 5 to 20 nm and a pore size of 3 to 15 nm.
[0048] Figure 4 This is a low-magnification SEM photograph of the cross section of the Nb coating-titanium alloy of the present invention.
[0049] like Figure 4As shown in the figure, the thickness of the Nb coating on the titanium alloy substrate is 24 μm. No obvious cracks were observed on the cross section of the Nb coating, and there was a clear transition and boundary between the Nb coating and the titanium alloy substrate, indicating that the Nb coating and the titanium alloy substrate are well bonded.
[0050] Figure 5 This is the EDS line scan spectrum of the Nb coating-titanium alloy of the present invention.
[0051] like Figure 5 As shown, EDS element analysis shows that the niobium element in the Nb coating is uniformly distributed along the depth direction, and obvious element transition can be observed at the junction of the Nb coating and the titanium alloy substrate, which can enhance the bonding strength between the Nb coating and the titanium alloy substrate.
[0052] Figure 6 It is a microhardness comparison diagram of the Nb coating-titanium alloy and the titanium alloy substrate of the present invention.
[0053] like Figure 6 As shown, after the Nb coating was introduced on the surface of the titanium alloy substrate, the microhardness of the Nb coating-titanium alloy surface was effectively improved.
[0054] The embodiment of the friction corrosion resistance test method of the biomedical titanium alloy modified by magnetron sputtering of the present invention is to test the friction corrosion resistance of the Nb coating-titanium alloy and the titanium alloy substrate using the micro-motion test device disclosed in the Chinese invention patent application with publication number CN108760618A, as follows:
[0055] A copper wire with a length of about 10 cm was welded on the back of the Nb coating-titanium alloy and the titanium alloy substrate to connect the working electrode to study its electrochemical characteristics, and the sample was encapsulated with epoxy resin, leaving only 10 mm 2 research surface.
[0056] The grinding pair material is CoCrMo alloy, which has a tensile strength of 1507MPa, a yield strength of 962MPa, an elongation of 20%, an elastic modulus of 200GPa, and a Poisson's ratio of 0.3; the mass fractions of each element are: 28.10wt% chromium, 5.90wt% molybdenum, 0.88wt% nickel, 0.65wt% iron, 0.63wt% manganese, 0.22wt% silicon, 0.25wt% carbon, 0.12wt% nitrogen, and 63.25% cobalt.
[0057] An electrochemical workstation was used to test the open circuit potential before and after the micromotion test and the polarization curve after the micromotion test. The electrochemical test used three electrodes, with the reference electrode being saturated Ag / AgCl, the counter electrode being a platinum electrode, and the working electrode being a coating-titanium alloy or a titanium alloy substrate.
[0058] The concentrations of the components in the simulated body fluid used are: Na + 142.0mM, K + 5mM, Mg 2+ 1.5mM, Ca 2+ 2.5mM, Cl - 147.8mM, HCO3 - 4.2mM, HPO4 2- 1.0mM, SO4 2- is 0.5mM.
[0059] The micro-motion tangential frequency was set to 1 Hz, the number of cycles was 3000, the sampling rate was 40 Hz, the normal load was 45 N, and the displacement amplitude was 45 μm. The pH of the simulated body fluid was kept at 7.4, and the volume of the corrosion solution required for each experiment was 100 mL.
[0060] Figure 7 It is a comparison chart of the friction coefficients of the Nb coating-titanium alloy and the titanium alloy substrate of the present invention.
[0061] like Figure 7 As shown, the Nb coating effectively reduces the friction coefficient of the titanium alloy substrate surface and improves the fretting wear resistance of the Nb coating-titanium alloy surface.
[0062] Figure 8 It is a comparison chart of the material loss of the Nb coating-titanium alloy and the titanium alloy substrate of the present invention.
[0063] like Figure 8 As shown, the introduction of Nb coating can reduce the material loss of Nb coating-titanium alloy by about 60% compared with the material loss of titanium alloy substrate, indicating that Nb coating significantly improves the wear resistance of Nb coating-titanium alloy.
[0064] Fig. 9 It is a comparison diagram of the open circuit potential of the Nb coating-titanium alloy and the titanium alloy substrate of the present invention.
[0065] like Fig. 9 As shown in the figure, before the friction starts, the open circuit potential of the Nb coating-titanium alloy is lower than that of the titanium alloy substrate, indicating that the Nb coating reduces the corrosion tendency of the Nb coating-titanium alloy surface. After the friction starts, the passive film on the material surface is destroyed, and the open circuit potential decreases, while the decrease in the open circuit potential of the Nb coating-titanium alloy is lower than that of the titanium alloy substrate, indicating that the Nb coating reduces the degree of damage and activity of the Nb coating-titanium alloy surface, thereby enhancing the corrosion resistance.
[0066] Fig.10 It is a comparison diagram of the polarization curves of the Nb coating-titanium alloy and the titanium alloy substrate of the present invention.
[0067] like Fig.10 As shown in the figure, the corrosion voltage of Nb coating-titanium alloy is -0.25V, and the corrosion current is 3.78μA; the corrosion voltage of titanium alloy substrate is -0.389V, and the corrosion current is 14.908μA. It can be seen that the introduction of Nb coating reduces the corrosion current and corrosion voltage values, and improves the corrosion resistance of Nb coating-titanium alloy surface.
[0068] The above is a description of the relevant contents of the present invention. A person skilled in the art will be able to implement the present invention based on these descriptions. Based on the above contents of the present invention, all other embodiments obtained by a person skilled in the art without creative work shall fall within the scope of protection of the present invention.
Claims
1. A biomedical titanium alloy modified by magnetron sputtering, comprising a titanium alloy substrate, characterized in that: Also included is a Nb coating located on the surface of the titanium alloy substrate.
2. The biomedical titanium alloy modified by magnetron sputtering according to claim 1, characterized in that: The thickness of the Nb coating is 22-25 μm.
3. The biomedical titanium alloy modified by magnetron sputtering according to claim 1, characterized in that: The Nb coating has a porous structure formed by the accumulation of nanoparticles with a particle size of 5 to 20 nm, and a pore diameter of 3 to 15 nm.
4. The biomedical titanium alloy modified by magnetron sputtering according to claim 1, characterized in that: The mass fractions of the elements in the titanium alloy substrate are: 6.05% aluminum, 3.95% vanadium, 0.11% iron, 0.014% carbon, 0.14% oxygen, 0.006% nitrogen, 0.001% hydrogen, and 89.729% titanium. The titanium alloy substrate has a tensile strength of 860 MPa, a yield strength of 795 MPa, an elongation of 12%, an elastic modulus of 110 GPa, and a Poisson's ratio of 0.3; The surface roughness of the titanium alloy substrate is Ra≤0.1 μm.
5. The method for preparing the biomedical titanium alloy modified by magnetron sputtering according to any one of claims 1 to 4, characterized in that: The following steps are involved: Titanium alloy substrate pretreatment; Using Nb metal sheet as target material, the surface of titanium alloy substrate as deposition surface, argon as working gas, Nb atoms in Nb metal sheet are sputtered onto the surface of titanium alloy substrate under the action of electric field, thus forming Nb coating on the surface of titanium alloy substrate.
6. The method for preparing a biomedical titanium alloy modified by magnetron sputtering according to claim 5, characterized in that: The purity of the Nb metal sheet is above 99.9%.
7. The method for preparing biomedical titanium alloy modified by magnetron sputtering according to claim 5, characterized in that: The titanium alloy substrate was pretreated as follows: first, it was polished on a polishing machine with 600#, 1000#, 1500#, and 2000# sandpaper in sequence; then, it was precisely polished with W2.5 diamond paste and a 3000# roughness cloth grinding disc; then, it was ultrasonically cleaned in anhydrous ethanol for two minutes; and then, it was pre-sputtered with argon for 30 minutes.
8. The method for preparing biomedical titanium alloy modified by magnetron sputtering according to claim 5, characterized in that: Radio frequency sputtering is used; the diameter of the Nb metal sheet is 50 mm and the thickness is 5 mm; the distance between the surface of the Nb metal sheet and the surface of the biomedical titanium alloy substrate is 40 mm; the working gas is argon, the purity of argon is 99.99%, and the argon flow rate is 80 sccm; the working pressure is 2 Pa, the discharge voltage is 200 V, the applied power is 200 W, the deposition time is 1500 min, and the sputtering angle is 25°.
9. The method for testing the friction and corrosion resistance of biomedical titanium alloy modified by magnetron sputtering according to any one of claims 1 to 4, characterized in that: The friction and corrosion test was carried out in a micro-motion test device with CoCrMo alloy as the grinding pair material in simulated body fluid.
10. The method for testing the friction and corrosion resistance of biomedical titanium alloy modified by magnetron sputtering according to claim 9, characterized in that: The tensile strength of CoCrMo alloy is 1507MPa, the yield strength is 962MPa, the elongation is 20%, the elastic modulus is 200GPa, and the Poisson's ratio is 0.3; The mass fractions of the elements in the CoCrMo alloy are as follows: 28.10wt% chromium, 5.90wt% molybdenum, 0.88wt% nickel, 0.65wt% iron, 0.63wt% manganese, 0.22wt% silicon, 0.25wt% carbon, 0.12wt% nitrogen, and 63.25wt% cobalt. The concentrations of the components in the simulated body fluid are: Na + 142.0mM, K + 5mM, Mg 2+ 1.5mM, Ca 2+ 2.5mM, Cl - 147.8mM, HCO3 - 4.2mM, HPO4 2- 1.0mM, SO4 2- is 0.5mM.
Citation Information
Patent Citations
Fretting test device
CN108760618A
Method for preparing anti-oxidation Nb coating on surface of carbon material
CN102127737A
Method for preparing Nb film by utilizing magnetron sputtering method
CN102864427A
Process for preparing corrosion resistant metal material through coating tantalum or niobium with PVD (physical vapor deposition) method
CN103695854A
Rotary seal member and method for making
US5484665A